SOSIALISASI PUPUK ORGANIK ECO FARMING RAMAH LINGKUNGAN TANAMAN HORTIKULTURA DI KELURAHAN EMPOANG UTARA KECAMATAN BINAMU KABUPATEN JENEPONTO - Andi Amran Asriadi; Firmansyah Firmansyah (Universitas Halu Oleo, 2021)
The purpose of this service is to provide farming communities with knowledge about the adverse effects of using inorganic fertilizers on the environment and consumers. Farming communities know how to use organic fertilizers appropriately so that they are able to provide high production yields without damaging the environment and consumer health. The method of implementing the service is carried out by means of lectures and discussing evaluations of community activities, especially farmers. The result of community service is an increase in residents' knowledge related to the use of organic fertilizers. In addition, it can also provide information on public awareness of the impact of soil fertility, inorganic fertilizers on the environment and health.